Molecular Cloning, Modeling, and Characterization of Type 2 Metallothionein from Plantago ovata Forsk. (13th March 2013) - Moulick, Amitava; Mukhopadhyay, Debashis; Talapatra, Shonima; Ghoshal, Nirmalya; Sen Raychaudhuri, Sarmistha
Abstract : Plantago ovata Forsk is a medicinally important plant. Metallothioneins are cysteine rich proteins involved in the detoxification of heavy metals. Molecular cloning and modeling of MT from P. ovata is not reported yet. The present investigation will describe the isolation, structure prediction, characterization, and expression under copper stress of type 2 metallothionein (MT2) from this species. The gene of the protein comprises three exons and two introns. The deduced protein sequence contains 81 amino acids with a calculated molecular weight of about 8.1 kDa and a theoretical pI value of 4.77. The transcript level of this protein was increased in response to copper stress. Homology modeling was used to construct a three-dimensional structure of P. ovata MT2. The 3D structure model of P. ovata MT2 will provide a significant clue for further structural and functional study of this protein.